Substantive Morphological Descriptions, Phylogenetic Analysis and Single Nucleotide Polymorphisms of Aspergillus Species From Foeniculum vulgare - Mahata, Pranab Kumar; Dass, Regina Sharmila; Pan, Archana; Muthusamy, Babylakshmi (Frontiers in Microbiology, 2022)
Ascomycetous fungi are found associated with a wide variety of substrates which range from fresh water to marine ecosystems, tropical to temperate forest soils and deserts, throughout the world over. These demystifying fungi exist as endophytes, pathogens and saprobes. They have been studied due to their ability to contaminate foods and feedstuffs, causing an elaboration of mycotoxins. The objectives of the study included extensive analyses of the morphological features of fungi, especially Aspergilli, which have been presented while studying them on specific mycological media. It is also an elaborate compilation of substantive macro- and micro-morphological characterization of different Aspergilli isolated from the spice Foeniculum vulgare used in India and other countries in the world. Further, a first of its kind attempt has been made to study their relative abundance and frequency of occurrence, molecular phylogeny and genetic relatedness to characterize the Aspergilli into specific sections, groups and clades. Single nucleotide polymorphism (SNP) analysis was carried out to evaluate the functional consequences of nucleotide variations, synonymous and non-synonymous mutations in the protein structure. The study resulted in a total of 3,506 Aspergillus isolates, which were obtained from seventy (70) fennel samples, representing 14 Aspergillus species. The two most frequently found species were A. niger and A. flavus with a relative abundance of 32.24 and 11.63%, respectively. The taxonomy and current placements have been reappraised with suggestions and prospects for future research from six sections namely Terrei, Flavi, Fumigati, Nidulantes, Nigri, and Versicolores. In addition, a total number of 27 isolates were studied and deposited at the National Centre for Biotechnology Information (NCBI) and five Aspergillus species have been identified and are being reported for the first time from the fennel seeds, based on partial sequence analysis of the official fungal barcode namely, Internal Transcribed Spacer (ITS) and a functional gene, beta tubulin gene locus, coupled with phenotypic characterization. SNPs for specific DNA regions have been used to identify variants in Aspergilli obtained from Indian fennel seeds for the first time. The need for a polyphasic approach of morphological identification and genetic characterization of Aspergilli from Foeniculum vulgare is addressed and presented here in adequate detail. Our current work makes extensive use of partial beta-tubulin gene sequences analyses to evaluate the association between SNPs in five Aspergillus species sections.